The Effect of Quantum Model to Students’ Learning Independence for Elementary School in Teaching Natural Science Learning - Sumiati Pulungan; Yanti Fitria (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this reserach was to find out the effect of quantum model to students learning independence for elementary school in teaching natural science learning. The research design was classroom action research. This research was done at SDN 060827 Medan with the subject of the research was 37 students of grade V. The data collection was using: observation and questionnaire. The data was described and elaborated by mixing some steps, they were collecting the data data reduction, data display and finally conclusion. The result of the research prove that there was effect of quantum model to students’ learning independence for elementary school in teaching natural science learning. Among of indicators, the highest score was motivation. Quantum model is very effective to use in teaching natural science learning for elementary school